Quantifying accuracy and heterogeneity in single-molecule super-resolution microscopy - Hesam Mazidi (Nature Portfolio, 2020)
Standard benchmarking of single-molecule localization microscopy cannot quantify nanoscale accuracy of arbitrary datasets. Here, the authors present Wasserstein-induced flux, a method using a chosen perturbation and knowledge of the imaging system to measure confidence of individual localizations.